RL-BLED: A Reversible Logic Design of Bit Level Encryption/Decryption Algorithm for Secure Mammogram Data Transmission - Guptha, M. N. Sharada; Eshwarappa, M. N. (Wireless personal communications, 2022)
Security is an essential task while focusing on confidential level of patient information during medical data transmission. The image encryption algorithms that considered bit-level permutation can provide better security by changing the position of the pixels concurrently. But these encryption algorithms consume more power and area while implementing it on FPGA for securing the mammographic images based on irreversible logic or conventional gate circuits. Instead, the reversible logic gates can save the power and increase the speed of computation. This work proposed a new bit level image encryption and decryption circuit using reversible logic gates (RL-BLED). The proposed encryption module contains key generation unit, diffusion unit and confusion unit. It used reversible logic (RL) gates for diffusing the binary sequences and permuting the bitplanes in the confusion phase based on the key generated using reversible chaotic sequence generator module. Each unit of the proposed RL-BLED depends on numerous reversible sub-modules including adders, rotators, multipliers, modulo operators, dividers and so on. Here, the quantum cost, garbage outputs, delay and power of each sub-modules are analysed for demonstrating the effectiveness of the RL-BLED structure. The simulation results illustrate that the suggested RL-BLED overtakes the existing models in terms of LUTs, slices, flip flops and frequency.